2020
DOI: 10.1080/14616734.2020.1828532
|View full text |Cite
|
Sign up to set email alerts
|

Video observations of maternal sensitivity in urban and Rural Iran: an exploratory study

Abstract: Aiming to contribute to the cross-cultural understanding of the nature and meaning of the sensitivity construct, this exploratory study observed 26 mothers and their 18-60-month-old children in rural ( 15) and urban Iran (11) for 30 minutes of free interaction in the home context. This first study to use video observations of parenting in Iran showed that mothers were generally comfortable with being filmed, intercoder reliability could be established for the Ainsworth sensitivity scale, and the full range of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…Research on economic deprivation and parenting generally shows that poverty and stress associated with its pressures can undermine parents’ ability to be supportive caregivers, with potentially negative consequences for children’s development ( Cooper et al, 2009 ; Mesman et al, 2012 ; Hoff-Ginsberg and Laursen, 2019 ; Dawson et al, 2020 ). However, studies that examined sensitivity in populations with very scarce economic resources reported mixed findings ( Mesman et al, 2018a ; Alsarhi et al, 2020 ; Asanjarani et al, 2020 ; Fourment et al, 2020 ). Exploring the levels and nature of parenting in Ethiopian families living in poverty is necessary to understand if there is variation within this population that might provide insights into sources of resilience that can be informative for interventions aiming to support parents and children ( Hoff-Ginsberg and Laursen, 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“…Research on economic deprivation and parenting generally shows that poverty and stress associated with its pressures can undermine parents’ ability to be supportive caregivers, with potentially negative consequences for children’s development ( Cooper et al, 2009 ; Mesman et al, 2012 ; Hoff-Ginsberg and Laursen, 2019 ; Dawson et al, 2020 ). However, studies that examined sensitivity in populations with very scarce economic resources reported mixed findings ( Mesman et al, 2018a ; Alsarhi et al, 2020 ; Asanjarani et al, 2020 ; Fourment et al, 2020 ). Exploring the levels and nature of parenting in Ethiopian families living in poverty is necessary to understand if there is variation within this population that might provide insights into sources of resilience that can be informative for interventions aiming to support parents and children ( Hoff-Ginsberg and Laursen, 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“…Within family contexts, a handful of studies have investigated the nature and predictors of CRB in parents and children. Studies in several non-Western countries video coded the CRB of mothers using a 3-point global coding scheme and found the percentage of mothers who display CRB to vary strongly between countries (Alsarhi et al, 2021;Asanjarani et al, 2021;Fourment et al, 2021;Lima Ribeiro et al, 2021;Mesman et al, 2021;Rahma et al, 2021). Children's CRB have been found to occur frequently (Barriage & Searles, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Children's CRB have been found to occur frequently (Barriage & Searles, 2019). Whereas mothers' CRB declined over the course of an observation (Asanjarani et al, 2021), children's CRB did not (Barriage & Searles, 2019). There is some evidence that younger parents show more CRB (Dawson et al, 2018;Mesman et al, 2021), and some fathers have reported to be more affected by observers than mothers (Russell et al, 1992).…”
Section: Introductionmentioning
confidence: 99%